Agenesis of the Inferior Vena Cava in H Syndrome Due to a Novel SLC29A3 Mutation. Issue 5 (14th February 2013) - Mutlu, Gül Yesiltepe; Ramot, Yuval; Babaoglu, Kadir; Altun, Gurkan; Zlotogorski, Abraham; Molho‐Pessach, Vered
Abstract We present a 10‐year‐old girl with typical clinical features of H syndrome. Complete agenesis of the inferior vena cava was found on echocardiography and radiologic studies. Mutation analysis of the SLC29A3 gene revealed a novel nonsense mutation. This unique case extends the clinical and mutation spectrum associated with H syndrome and underlines the importance of routine cardiac screening in this disorder.